A THEMATIC GROUP IS «METHODS OF EARNING OF MONEY» HOW THE PHRASEOLOGICAL FRAGMENT OF REALITY IS IN POLISH, UKRAINIAN AND ENGLISH LANGUAGES - Kraychynska, G. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article is devoted to the descrіsption of the numismatic phraseological units in Polish, Ukrainian and English languages, their functional analysis is made.